Preoperative Airway Management Checklist: The Transfer of Knowledge Into Clinical Practice by Video-based Feedback - Tahsin Şimşek; Mehmet Yılmaz; Ayten Saraçoğlu; Kemal Tolga Saraçoğlu (Southern Clinics of Istanbul Eurasia, 2020)
INTRODUCTION[|]A preoperative checklists guide was issued in 2008 by the American Society of Anesthesiologists (ASA) to improve patient safety. We aimed to determine the applicability and effectiveness of video-based feedback for the transfer of knowledge into clinical practice by using this guide.[¤]METHODS[|]Ten anesthesia residents were divided into two groups according to their seniority, under two years and over two years. Once the preparation, anesthesia induction and airway management steps were completed, video-based feedback was given according to the ASA checklist. The knowledge level and skills of the residents were evaluated. Two months after the video-based feedback, all steps were repeated in another patient. The results were compared with a checklist score. Each guideline item was analyzed.[¤]RESULTS[|]The ages of participants varied between 27–34 years (28.9+-2.28 years), five were female, and five were male. Results of the pre and post video-based feedback evaluations of the residents were statistically similar in the senior and junior groups. The post-feedback achievement score in both groups was significantly higher than the pre-feedback achievement score (p<0.05).[¤]DISCUSSION AND CONCLUSION[|]It has been shown that the ASA Checklist Procedure before airway management during general anesthesia induction can be successfully put into clinical practice with video-based feedback. We concluded that patient safety could be increased by the integration of this method into the routine anesthesia resident training program.[¤]